2021
DOI: 10.1136/bmjopen-2021-052737
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of adverse drug reactions at an adverse drug reaction monitoring centre in Central India: a 7-year surveillance study

Abstract: ObjectivesTo analyse and present the occurrence and severity of spontaneous adverse drug reaction (ADR) reports prospectively registered at an ADR monitoring centre (AMC) in Central India.Setting and dataThe survey was conducted between 2013 and 2019 at an ADR Monitoring Centre in Central India. ADRs were recorded using the standard ‘Suspected ADR Reporting form’.Outcome measuresThe causality of the ADRs were categorised using the WHO causality assessment scale to assess the relationship between a drug and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…About 69.65% of the ADRs were Type B (69.649%), and one was Type F (telmisartan, aldactone), Type C (Amlodipine induced gingival hypertrophy) each. These findings were consistent with other studies that reported an increased incidence of Type B cutaneous manifestations 21,22 .…”
Section: Fig 6: Duration Involved For Recovery From the Adrsupporting
confidence: 93%
“…About 69.65% of the ADRs were Type B (69.649%), and one was Type F (telmisartan, aldactone), Type C (Amlodipine induced gingival hypertrophy) each. These findings were consistent with other studies that reported an increased incidence of Type B cutaneous manifestations 21,22 .…”
Section: Fig 6: Duration Involved For Recovery From the Adrsupporting
confidence: 93%
“…In our study, the majority of adverse drug reactions (ADRs) were classified as Type A according to Rawlins and Thompson's classification, consistent with the established observation that approximately 80% of ADRs fall into this category, while the remaining 20% are categorized as Type B 23 . This finding is further substantiated by two additional studies 24,25 . Causality assessment using Naranjo's Algorithm 11 indicated that probable ADRs accounted for 56.36% of cases, similar to the findings of some another literature studies 24 .…”
Section: Resultssupporting
confidence: 55%
“…Antimicrobials drew attention as the class most involved in suspicions (29%). Among the relevant AEs found, "multidrug resistance" was related to ceftriaxone/tazobactam (n = 15; 0.76%; the Not Recommended category) and amikacin (n = 9; 0.45%; Access) [112].…”
Section: Pv As a Tool To Identify The Ineffectiveness Of Antibioticsmentioning
confidence: 99%